Bimbingan Karir sebagai Upaya Peningkatan Motivasi Siswa dalam Menggapai Cita - cita di SMAN 3 Kefamenanu - Amrulloh, Mohamad Fajar Farid; Handayani, Rika; Priyambodo, Hernur Yoga; Fitriani (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
The problem faced by high school students nearing graduation, aside from the final exams, is the confusion in choosing a career path after completing high school. This confusion arises due to the lack of information and guidance regarding students' potential, aspirations, and the paths to achieve their goals. One of the options is continuing their studies, and thus, there is a need for information about study programs and universities that align with the students' potential. SMAN 3 Kefamenanu is one of the schools in the city of Kefamenanu that has a strong willingness to boost motivation so that students are enthusiastic about continuing their studies. The Career Guidance and Counseling Program (PKM Career Guidance) aims to provide information, guidance, and be a discussion partner for consulting on how to discover one's potential and make career choices based on interests and abilities. The methods employed include presentations, Q&A sessions, guid`ance, and discussions. The results of the service show that after consulting, 74% of students are interested in continuing their studies, 13% are employed, and 13% entered a Catholic academy. The career guidance socialization activities related to information about study programs, job prospects, and universities have a significant impact on providing information for further studies. It also increases students' interest in continuing their education to pursue their aspirations. This is evidenced by questionnaire results, with the percentage of students having sufficient information about further studies before the socialization being 42% (fair), and after the socialization, it reaches 98% (very good). Similarly, the percentage of students showing interest before the socialization is 46% (fair), and after the socialization, it reaches 95% (very good).